PEMUTUSAN HUBUNGAN KERJA AKIBAT KESALAHAN BERAT PADA PERJANJIAN KERJA BERSAMA FEDERASI SERIKAT BURUH SOLIDARITAS INDONESIA DENGAN PT. PEC-TECH SERVICE INDONESIA PANGKALAN KERINCI - Bima Sakti Ginting; Maryati Bachtiar; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
An employment relationship is a manifestation of a work agreement. In practice, the employment relationship between employers and workers or laborers often experiences problems that can lead to termination of employment. As in the case that happened at PT. Pech Tech Service Indonesia, workers are terminated because they are considered to have committed serious mistakes and do not get their rights. Termination of employment is often carried out unilaterally by employers against workers. Various reasons are always used as arguments for employers, including making the Collective Labor Agreement a tool for terminating employment of workers, and one of them is when workers are deemed to have committed grave mistakes as stated in Article 158 paragraph 1 of Law Number 13 Year 2003 Concerning Manpower. This article is always used as a reference for employers to terminate employment.In the case of workers committing serious mistakes, employers often terminate the employment relationship unilaterally, even though according to the Decision of the Constitutional Court Number 012 / PUU-I / 2003, dated 28 October 2004 Article 158 is declared contrary to the 1945 Constitution and has no power. binding law. Basically, the serious mistakes regulated in Article 158 are categorized as illegal acts or crimes regulated in the second book of the Criminal Code (KUHP). Therefore, the settlement of the Termination of Employment due to this serious mistake must pay attention to two things. Namely, termination of employment can be carried out after a criminal decision has permanent legal force and is found guilty, or if the worker is detained and unable to carry out his obligations, the provisions of Article 160 of Law Number 13 Year 2003 concerning Manpower apply.The purpose of this research is to find out the mechanism of termination of employment due to serious mistakes according to legislation and to know the legal protection of workers or laborers who have terminated their employment. And as a suggestion from the author, so that employers can pay attention to the Constitutional Court Decision and Ministerial Circular to terminate employment. In the case of the making of a Collective Labor Agreement, the trade union and labor union can pay more attention to the content of article by article so that it does not become a detrimental impact on workers and trade unions or laborers in the future.Keywords: Termination of Employment, Due to Serious Errors, Collective Labor Agreement, Labor Union or Worker Union.